PERAN KOMUNITAS LOKAL DALAM MEMBANGUN PARIWISATA BERKELANJUTAN (STUDI KASUS LUMBUNG STROBERI) - Ayu Dyah Amelia; Ety Dwi Susanti (Journal Publicuho, 2024)
Sustainable tourism has become a primary focus in the context of sustainable development at various tourist attractions. This study aims to understand the role played by the local community in efforts towards sustainable tourism development, using the case study of Lumbung Stroberi. The research method used is a qualitative approach, which includes in-depth interviews, participatory observation, and document studies for data collection. The results of this study indicate that the local community is actively involved in destination management, preserving the environment, empowering the local economy, and promoting and preserving local cultural heritage. From this research, it can be concluded that close cooperation between the government, the tourism sector, and the local community is crucial in formulating concrete steps to achieve sustainable tourism development at tourist attractions such as Lumbung Stroberi.